2014
DOI: 10.1097/inf.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Prevention of Infection in Preterm Neonates by Topical Emollients

Abstract: Skin condition deteriorated progressively after birth and compromised skin condition increased the risk of infection. Emollients preserved skin integrity and thus prevented infection in preterm neonates. To optimize benefits of emollients for the prevention of bloodstream infection, use of emollients should begin immediately after birth when the skin is still intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 23 publications
0
40
0
6
Order By: Relevance
“…aureus on the lesions of infants and adults with AD was reduced by 50–78% after a twice-daily application of emollients, including ointments, coconut oil, or olive oil for 1–4 months [ 23 , 24 ]. Accordingly, use of emollients in preterm neonates reduced the risk for skin infections [ 25 ]. In contrast, an observational study of children with AD in New Zealand showed no association between emollient use and S .…”
Section: Introductionmentioning
confidence: 99%
“…aureus on the lesions of infants and adults with AD was reduced by 50–78% after a twice-daily application of emollients, including ointments, coconut oil, or olive oil for 1–4 months [ 23 , 24 ]. Accordingly, use of emollients in preterm neonates reduced the risk for skin infections [ 25 ]. In contrast, an observational study of children with AD in New Zealand showed no association between emollient use and S .…”
Section: Introductionmentioning
confidence: 99%
“…Topically applied oils could provide a physical barrier to skin disruption and/or accelerate and/or augment skin barrier development, resulting in reduced microorganism invasion, hospital-acquired infections and associated mortality 12–14. A recent analysis of data from Bangladesh suggested that preservation of skin integrity was associated with reduced risk of infection 15. Skin applications of emollients can also reduce transepidermal water loss16 17 and conserve heat and energy to promote physical growth 18.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trial of oil massage of preterm infants with coconut oil has produced similar results. 79 While an emollient appears to work by preserving skin integrity and protecting from skin injury, 80,81 this intervention is also hypothesized to work by helping accelerate maturation of skin-barrier function (partially through reducing cutaneous signs of essential fatty acid deficiency), thereby reducing likelihood of transcutaneous acquisition of invasive pathogens. Ongoing randomized community-based trials are addressing these questions in large rural populations in Nepal and India.…”
Section: Topical Emollient Therapymentioning
confidence: 98%